THE CAPACITY OPTIMIZATION OF BEAM ULTIMATE MOMENT ON PLANE FRAME - Layang, Samuel (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
The purpose of this research is to determine the effect of beam length on the ultimate moment occurs especially in plane frame that carries concentrated load and uniform load. This research used a plane frame as a model with calculating upon length of beam from center to center of column and clear length of beam. Concentrated load acting on the beam starting from 2.5 tons with an increase of 25% in two times respectively. Uniform force acts on the beam starting from 1 ton/m with an increase of 12.5% in two times respectively. The result of this research indicates that the plane frame that received concentrated load in level 1, the average reduction of ultimate moment is 6,070 % for live load and 6,811 % for combination load. On level 2, the average reduction of ultimate moment is 4,895 % for live load and 6,252 % for combination load. Plane frame with uniform load in level 1, the average reduction of ultimate moment is 11,458 % for live load and 11,316 % for combination load. On level 2, the average reduction of ultimate moment is 12,181 % for live load and 12,212 % for combination load.